The Ancient Maya of Mexico : Reinterpreting the Past of the Northern Maya Lowlands - Braswell, Geoffrey E. (Approaches to anthropological archaeology., 2014)
The archaeological sites of Mexico''s Yucatan peninsula are among the most visited ancient cities of the Americas. Archaeologists have recently made great advances in our understanding of the social and political milieu of the northern Maya lowlands. However, such advances have been under-represented in both scholarly and popular literature until now. ''The Ancient Maya of Mexico'' presents the results of new and important archaeological, epigraphic, and art historical research in the Mexican states of Yucatan, Campeche, and Quintana Roo. Ranging across the Middle Preclassic to the Modern peri.